Reinforced flame-retardant cellulose aerogel material and preparation method thereof
By combining polycarboxylic acid modified elolite with cellulose aerogel, the modified elolite/cellulose composite aerogel material is formed, which solves the problems of poor mechanical properties and flammability of cellulose aerogel materials, and the combination of high mechanical properties and excellent flame retardant properties is achieved.
Patent Information
- Application Number
- CN202411789858.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-04
AI Technical Summary
The poor mechanical properties and flammability of existing cellulose aerogel materials limit their application in multiple fields.
By using polycarboxylic acid as crosslinking agent, elosite and cellulose aerogel are combined to form a modified elosite/cellulose composite aerogel material, enhancing the binding force between inorganic elosite and organic cellulose, and building a dual network structure and graded porosity.
The mechanical properties and flame retardant properties of the composite aerogel are significantly improved, with a compressive strength of 3.6MPa, and 2.3MPa after the fire resistance test. The materials have a wider application in the fields of petroleum leakage treatment, thermal insulation and energy saving, biomedical and catalytic support.
Smart Images

Figure CN119552412A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogel materials, and in particular relates to a reinforced flame-retardant cellulose aerogel material and a preparation method thereof. Background Art
[0002] As a new third-generation aerogel, cellulose aerogel not only has many advantages of traditional aerogels, such as high specific surface area, high porosity, low density and low thermal conductivity, but also has some unique properties of cellulose aerogel, including biodegradability, green and pollution-free, and biocompatibility. It has broad application prospects in many fields, such as oil spill treatment, thermal insulation and energy saving, as well as biomedicine and catalytic carriers.
[0003] Halloysite nanotubes (HNTs) are a natural hollow aluminosilicate clay belonging to the kaolinite family. They have good crystallinity, low price, and wide distribution. They are used in the field of nano-templates due to their unique nanotube structure. In addition, due to their own characteristics, HNTs are also used in composites with polymers and high-molecular materials to improve the mechanical strength and thermal stability of composite materials. In the method of improving the bonding strength of composite materials, there are basically no reports on other cross-linking agents except for the addition of silane coupling agents. However, silane coupling agents were originally a type of cross-linking agent used for inorganic interface bonding, and the reaction cross-linking between cellulose is not ideal. Therefore, a better choice of cross-linking agent should be made to enhance the bonding strength between halloysite and cellulose.
[0004] Compared with other cellulose materials, straw cellulose has inherent defects such as a lower aspect ratio and poorer mechanical properties, which limit the large-scale application of straw-based cellulose aerogels. In addition, as a natural polymer, cellulose does not melt at high temperatures, burns rapidly when exposed to open flames, spreads flames quickly, and has low smoke toxicity. The poor mechanical properties and flammability of cellulose aerogels limit their application in many fields. Therefore, it is of great significance to seek a cellulose aerogel material with good mechanical properties and flame retardancy. Summary of the invention
[0005] The purpose of the present invention is to overcome the above technical deficiencies, provide a reinforced flame-retardant cellulose aerogel material and a preparation method thereof, and solve the technical problems of poor mechanical properties and flammability of cellulose aerogel in the prior art.
[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a method for preparing a reinforced flame-retardant cellulose aerogel material, comprising the following steps: S1, preparing a polycarboxylic acid solution with polycarboxylic acid, a catalyst and water as raw materials, placing halloysite in the polycarboxylic acid solution and stirring, and then calcining and post-treating to obtain polycarboxylic acid-modified halloysite; S2, adding the polycarboxylic acid-modified halloysite to the cellulose solution to obtain a mixed solution, and subjecting the mixed solution to an aging replacement treatment to obtain a wet gel; and drying the wet gel to obtain a reinforced flame-retardant cellulose aerogel material.
[0007] In a second aspect, the present invention provides a reinforced flame-retardant cellulose aerogel material prepared by the above preparation method.
[0008] Compared with the prior art, the beneficial effects of the present invention include: The present invention selects low-priced and widely available halloysite clay as the raw material for enhancing the flame retardancy of cellulose aerogel, and uses polycarboxylic acid as a cross-linking agent to enhance the bonding force between inorganic halloysite and organic cellulose, thereby solving the problem of inorganic-organic composites being bonded only by hydrogen bonds or physical overlaps. By compounding halloysite with cellulose aerogel, not only can the material have certain flame retardancy and heat insulation properties, but the introduction of halloysite also allows cellulose to be entangled and cross-linked with the modified halloysite as a skeleton, which is conducive to the formation of a quasi-double network structure and the formation of graded porosity, which can greatly improve the porosity of the composite aerogel, and at the same time effectively improve the mechanical properties and flame retardancy of the obtained material, making it have a wider application in the fields of oil spill treatment, thermal insulation and energy saving, as well as biomedicine and catalytic carriers. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 It is a schematic diagram of the mechanism of action of the present invention; Figure 2 This is a scanning electron microscope image of the enhanced flame-retardant cellulose aerogel material prepared in Example 1; Figure 3 This is a scanning electron microscope image of the reinforced flame-retardant cellulose aerogel material prepared in Example 1 after the fire resistance test. DETAILED DESCRIPTION
[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0011] In a first aspect, the present invention provides a method for preparing a reinforced flame-retardant cellulose aerogel material, comprising the following steps: S1, preparing a polycarboxylic acid solution with polycarboxylic acid, a catalyst and water as raw materials, placing halloysite in the polycarboxylic acid solution and stirring, and then calcining and post-treating to obtain polycarboxylic acid-modified halloysite; S2, adding polycarboxylic acid modified halloysite to the cellulose solution to obtain a mixed solution, subjecting the mixed solution to an aging replacement treatment to obtain a wet gel; and drying the wet gel to obtain a reinforced flame-retardant cellulose aerogel material.
[0012] Preferably, in step S1, the concentration of the polycarboxylic acid in the polycarboxylic acid solution is 1.0 mol / L to 1.1 mol / L, the mass concentration of the catalyst is 4 to 7%; and the mass ratio of halloysite to the polycarboxylic acid solution is 1:(18 to 22).
[0013] Preferably, in step S1, the polycarboxylic acid includes glutaric acid or adipic acid; and the catalyst includes sodium hypophosphite.
[0014] Preferably, in step S1, halloysite is a silicate mineral having a tubular shape, an outer diameter of 40 to 60 nm, and a length of 700 to 1500 nm.
[0015] Preferably, in step S1, halloysite is placed in a polycarboxylic acid solution and stirred for 1 to 2 hours, then dried and calcined; the calcination is performed at 150 to 180° C. for 5 to 10 minutes. In the present invention, water in the polycarboxylic acid solution is first dried out to increase the reaction effect, and then the polycarboxylic acid reacts with the Si-OH bond on the surface of the halloysite under the condition of high temperature calcination at 150 to 180° C., and is bonded to the surface of the halloysite by ester bonds.
[0016] More preferably, the post-treatment includes washing and drying, and the drying temperature is 80-100° C. In the present invention, the excess acid and catalyst not participating in the reaction are washed away by washing.
[0017] Preferably, in step S2, the mass ratio of polycarboxylic acid-modified halloysite to cellulose in the cellulose solution is (5-20):100.
[0018] Preferably, in step S2, the preparation step of the cellulose solution includes: precooling the alkaline urea aqueous solution to -8 to -16 °C and storing it for 2 to 4 hours, then placing the cellulose in the precooled alkaline urea aqueous solution, stirring at -2 to -6 °C for 1 to 2 hours to obtain a dissolved cellulose solution; the mass ratio of the alkaline urea aqueous solution to the cellulose is 600: (18 to 24). Hydrogenation of sodium hydroxide solution at room temperature will cause the cellulose fibers to swell anisotropically, the fibers will shrink longitudinally and increase in diameter, and at the same time, the lattice will undergo certain changes, causing irreversible changes in the cellulose aggregation structure. Therefore, the present invention precools the alkaline urea aqueous solution to facilitate the dissolution of cellulose and avoid anisotropic swelling of cellulose fibers, and then controls the stirring and dispersing temperature to improve the efficiency of uniform dispersion.
[0019] Further preferably, the alkaline urea aqueous solution comprises NaOH / urea / water solution, and the mass ratio of NaOH, urea and water is (6-8):(10-14):(78-86), more preferably 7:12:81.
[0020] Further preferably, the cellulose is straw-based cellulose prepared by an acid-base two-step method with a cross-sectional size of 5 to 20 nm, a length of 10 to 1000 nm, and an aspect ratio of (1 to 100):1.
[0021] Preferably, in step S2, the conditions for mixing the polycarboxylic acid-modified halloysite with the cellulose solution include: mixing for 30 to 60 minutes at an ultrasonic power of 50 to 300 W.
[0022] Preferably, in step S2, the aging replacement treatment is to place the mixed solution in an alcohol solvent and soak it at room temperature for 12 hours to 24 hours to form a wet gel; wherein, when the mixed solution is soaked in the alcohol solvent, it is sufficient to ensure that the formed wet gel is completely immersed; the alcohol solvent includes an ethanol solution or tert-butanol with a concentration of more than 95%; after the wet gel is formed, other replacement fluids such as deionized water can also be added for replacement treatment. During the replacement process, in order to ensure that more NaOH and urea small molecules in the wet gel are replaced, the replacement fluid can be replaced 3 to 5 times as needed, and when the alcohol solvent and the replacement fluid are the same, such as using an ethanol solution or tert-butanol, aging and replacement are carried out simultaneously.
[0023] Preferably, in step S2, the drying method includes CO 2 Supercritical drying. CO 2 Supercritical drying is to open the carbon dioxide supercritical drying equipment, wait for the carbon dioxide to cool to the set temperature of -3°C, and when the temperature of the autoclave reaches the set temperature of 45°C, the wet gel is quickly taken out and placed in the autoclave. The set temperature and pressure of the autoclave are 45°C and 8.0 MPa, respectively.
[0024] In a second aspect, the present invention provides a reinforced flame-retardant cellulose aerogel material prepared by the above preparation method.
[0025] See also Figure 1 , the main mechanism of action and advantages of the present invention: The present invention firstly uses polycarboxylic acid to modify halloysite, and prepares a cellulose solution by an alkaline solution system, uniformly mixes the halloysite and the cellulose solution, crosslinks, ages, and dries to obtain a reinforced flame-retardant cellulose aerogel material. Among them, polycarboxylic acid is a class of multifunctional compounds, which can react with -OH in cellulose to produce covalent bonds, and at the same time as the ester bond is formed, a certain amount of free carboxylic acid group -COOH can be introduced into cellulose, and -COOH can also covalently bond with Si-OH on the surface of halloysite. The present invention solves the problem that the inorganic-organic interaction mode in most composite materials can only be physically attached or hydrogen-bonded by polycarboxylic acid modification of a large number of hydroxyl groups on the surface of halloysite, and greatly improves the binding area and force between cellulose and halloysite; by adding modified halloysite, a large number of binding sites are provided for cellulose, so that cellulose wraps around the halloysite and forms a three-dimensional network structure, thereby enhancing the mechanical properties and flame retardant properties of the composite aerogel.
[0026] Therefore, the reinforced flame-retardant cellulose aerogel material of the present invention uses halloysite with high mechanical strength and good thermal stability as a reinforcing material, and uses polycarboxylic acid as a cross-linking agent to enhance the binding force between inorganic halloysite and organic cellulose under the catalysis of sodium hypophosphite catalyst, thereby realizing chemical bond bonding between inorganic and organic substances, and the chemical bond bonding is a covalent bond with a larger intermolecular force, rather than a hydrogen bond with a smaller force, and combined with the formed three-dimensional network structure, the mechanical properties and flame retardant properties of the aerogel are effectively improved, and the compressive strength reaches up to 3.6MPa. After the fire resistance test (burning with an alcohol lamp for 20 seconds), the compressive strength is still 2.3MPa, and the aerogel without halloysite is burned out. In addition, the preparation process of the present invention is simple and the raw material cost is low.
[0027] The present invention is further described in detail below through specific examples.
[0028] Example 1 (1) A polycarboxylic acid solution was prepared using glutaric acid, sodium hypophosphite as an esterification reaction catalyst and water as raw materials, wherein the concentration of glutaric acid was 1.03 mol / L and the concentration of sodium hypophosphite was 6 wt% (w / w); 2 g of halloysite was placed in 40 g of glutaric acid aqueous solution and stirred for 1.5 h, dried at 80° C. and then baked at 160° C. for 10 min, the excess acid and catalyst that did not participate in the reaction were washed away with water, and then dried at 80° C. to obtain glutaric acid-modified halloysite.
[0029] (2) Prepare 600 g of NaOH / urea / water solution with a mass ratio of 7:12:81, precool to -12 °C and store for 2 h. Place 20 g of cellulose in the NaOH / urea / water solution and stir at -4 °C for 1.5 h to obtain a dissolved cellulose solution; 2 g of glutaric acid-modified halloysite was added to the cellulose solution, i.e., the mass ratio of glutaric acid-modified halloysite was 10% of the cellulose, and the mixture was ultrasonically mixed for 30 min. At room temperature, the mixture was aged in an ethanol solution (analytical purity, 95%) for 12 h to form a wet gel, and at the same time, the NaOH / urea small molecules in the wet gel were replaced in the ethanol solution (to ensure the replacement effect, the ethanol solution was replaced 3 times), and then the mixture was subjected to CO 2 After supercritical drying (autoclave temperature of 45°C and pressure of 8 MPa), a reinforced flame-retardant cellulose aerogel material was obtained, which was recorded as modified HNTs / cellulose composite aerogel.
[0030] The mechanical properties of the obtained HNTs / cellulose composite aerogel were tested using an MWD-50A computer-controlled universal material testing machine. The test sample was a cylindrical block with a diameter of 25 mm and a height of 30 mm. The results showed that the compressive strength of the prepared composite aerogel material reached 3.5 MPa; after the fire resistance test (burning with an alcohol lamp for 20 seconds), the compressive strength was still 2.1 MPa.
[0031] The prepared modified HNTs / cellulose composite aerogel and the microscopic morphology of the material surface after the fire test were observed using the Nanosem430 field emission scanning electron microscope of Philips in the Netherlands. Figure 2 and Figure 3 shown.
[0032] like Figure 2 As shown in the figure, in the modified HNTs / cellulose composite aerogel, cellulose is entangled and cross-linked with halloysite as the skeleton, and a network pore structure is successfully constructed with a pore size at the mesoporous scale. The halloysite tubes overlapped into a three-dimensional network are evenly dispersed in the cellulose three-dimensional network pores. After the fire resistance test, Figure 2 As shown, the material structure has not collapsed, and the halloysite still maintains its original skeleton, providing a certain force support.
[0033] Comparative Example 1 The only difference from Example 1 is that modified halloysite is not added, and the other steps and conditions are the same as those in Example 1.
[0034] The results showed that the aerogel without halloysite was completely burned out after the fire test.
[0035] Comparative Example 2 The only difference from Example 1 is that 2 g of unmodified halloysite is added to the cellulose solution. The other steps and conditions are the same as those in Example 1.
[0036] The results show that the prepared composite aerogel material has a compressive strength of 1.5MPa, and after the fire test, the compressive strength is 0.7MPa. The compressive strength and mechanical properties after the fire test are significantly lower than those in Example 1. This comparative example only does not modify the halloysite with a crosslinker, which can verify that the addition of the crosslinker forms a chemical bond between cellulose and halloysite, changing the interaction mode that can only be physically attached or hydrogen-bonded in traditional composite materials, greatly increasing the bonding area and force between cellulose and halloysite. Because cellulose and halloysite are not tightly combined, the cellulose aerogel skeleton is more easily burned, which further causes a decrease in mechanical properties after the fire test.
[0037] Comparative Example 3 The only difference from Example 1 is that benzoic acid is used to replace glutaric acid to modify the halloysite, and the other steps and conditions are the same as those in Example 1.
[0038] The results show that the compressive strength and mechanical properties of the prepared composite aerogel material after the fire test are similar to those of Comparative Example 2. This is because benzoic acid has only one -COOH group in its chemical structure. Although it undergoes an esterification reaction with Si-OH to produce a covalent bond during the halloysite modification process, there is no excess -COOH to cross-link with the -OH in cellulose, so no performance improvement is achieved.
[0039] Example 2 The only difference from Example 1 is that 3 g of halloysite modified with glutaric acid is added to the cellulose solution, that is, the mass proportion of the halloysite modified with glutaric acid is 15% of the cellulose. Other steps and conditions are the same as those in Example 1.
[0040] The prepared modified HNTs / cellulose composite aerogel has a compressive strength of 2.7 MPa, and after the fire resistance test, the compressive strength is 1.1 MPa.
[0041] Example 3 (1) A polycarboxylic acid solution was prepared using adipic acid, sodium hypophosphite as an esterification reaction catalyst and water as raw materials, wherein the concentration of adipic acid was 1.0 mol / L and the concentration of sodium hypophosphite was 6 wt %. 2 g of halloysite was placed in 40 g of an aqueous solution of adipic acid and stirred for 2 h. The solution was dried at 100 ° C and then baked at 180 ° C for 5 min to wash away excess acid and catalyst that did not participate in the reaction. The solution was then dried at 100 ° C to obtain adipic acid-modified halloysite.
[0042] (2) Prepare 600 g of NaOH / urea / water solution with a mass ratio of 7:12:81, precool to -14 °C and store for 4 h. Place 20 g of cellulose in the NaOH / urea / water solution and stir at -4 °C for 1 h to obtain a dissolved cellulose solution; 2 g of halloysite modified with adipic acid was added to the cellulose solution, with the mass ratio of adipic acid-modified halloysite being 10% of the cellulose, and the mixture was ultrasonically mixed for 60 min. The mixture was aged in ethanol (analytical purity, 95%) for 18 h at room temperature to form a wet gel, and the NaOH / urea small molecules in the wet gel were replaced in the ethanol solution. 2 The HNTs / cellulose composite aerogel was obtained after supercritical drying (autoclave temperature of 45 °C and pressure of 8 MPa).
[0043] Example 4 (1) A polycarboxylic acid solution was prepared using glutaric acid, sodium hypophosphite as an esterification reaction catalyst and water as raw materials, wherein the concentration of glutaric acid was 1.1 mol / L and the concentration of sodium hypophosphite was 6 wt %. 2 g of halloysite was placed in 40 g of glutaric acid aqueous solution and stirred for 1 h. The mixture was dried at 90° C. and then baked at 160° C. for 10 min. The excess acid and catalyst that did not participate in the reaction were washed away. The mixture was then dried at 90° C. to obtain glutaric acid-modified halloysite.
[0044] (2) Prepare 600 g of NaOH / urea / water solution with a mass ratio of 7:12:81, precool to -12 °C and store for 3 h. Place 20 g of cellulose in the NaOH / urea / water solution and stir at -2 °C for 2 h to obtain a dissolved cellulose solution; 2 g of glutaric acid-modified halloysite was added to the cellulose solution, i.e., the mass ratio of glutaric acid-modified halloysite was 10% of the cellulose, and the mixture was ultrasonically treated for 30 min. At room temperature, the mixture was aged in tert-butyl alcohol (analytical purity, 99.5%) for 12 h to form a wet gel, and at the same time, the NaOH / urea small molecules in the wet gel were replaced in the tert-butyl alcohol solution. 2 The HNTs / cellulose composite aerogel was obtained after supercritical drying (autoclave temperature of 45 °C and pressure of 8 MPa).
[0045] Example 5 (1) A polycarboxylic acid solution was prepared using adipic acid, sodium hypophosphite as an esterification reaction catalyst and water as raw materials, wherein the concentration of adipic acid was 1.05 mol / L and the concentration of sodium hypophosphite was 6 wt %. 2 g of halloysite was placed in 40 g of an aqueous solution of adipic acid and stirred for 1.5 h. The mixture was dried at 80° C. and then baked at 160° C. for 10 min. The excess acid and catalyst that did not participate in the reaction were washed away. The mixture was then dried at 80° C. to obtain adipic acid-modified halloysite.
[0046] (2) Prepare 600 g of NaOH / urea / water solution with a mass ratio of 7:12:81, precool to -16 °C and store for 2 h. Place 20 g of cellulose in the NaOH / urea / water solution and stir at -4 °C for 1 h to obtain a dissolved cellulose solution; 2 g of halloysite modified with adipic acid was added, and the mass ratio of halloysite modified with adipic acid was 10% of cellulose. The mixture was ultrasonically mixed for 45 min. The mixture was aged in tert-butyl alcohol (analytical purity, 99.5%) for 24 h at room temperature to form a wet gel. At the same time, the NaOH / urea small molecules in the wet gel were replaced in the tert-butyl alcohol solution. 2 The HNTs / cellulose composite aerogel was obtained after supercritical drying (autoclave temperature of 45 °C and pressure of 8 MPa).
[0047] The compressive strength test results of the composite aerogels obtained in the above embodiments and comparative examples and the compressive strength test results after the fire test are statistically analyzed, as shown in Table 1 below.
[0048] Table 1 Mechanical properties and fire resistance of composite aerogels
[0049] As can be seen from Table 1, the modified HNTs / cellulose composite aerogels provided by the present invention have greatly improved mechanical properties, with a compressive strength of 2.7 to 3.6 MPa, and also have excellent flame retardant properties. After the fire test, the compressive strength can still be maintained at 1.1 to 2.3 MPa.
[0050] And the performance of Example 1 is better than that of Example 2 because the addition amount of 10% of modified halloysite is optimal, and a complete skeleton structure is built as a whole. After being entangled with cellulose molecules, the compressive strength is significantly improved. In the fire-resistant test, although the cellulose on the surface of the material is burned and destroyed, the cellulose in the middle of the sample forms a thick carbon layer on the surface of the halloysite skeleton, which reduces the entry of oxygen. It is not ignited, the structure is not destroyed, and the loss of compressive strength is relatively small. In Example 2, the addition amount of 15% of modified halloysite is relatively high, and the cellulose is limited. It cannot completely entangle the halloysite skeleton. Some halloysite appears loosely stacked, and the porosity of the material is reduced. In the fire-resistant experiment, due to the reduction in porosity, the thermal insulation effect of the material is reduced, the internal aerogel structure is destroyed, and the mechanical properties are reduced.
[0051] Different from the prior art, the present invention provides a reinforced flame-retardant cellulose aerogel material and a preparation method thereof. The aerogel uses halloysite with high mechanical strength and good thermal stability as a reinforcing material. The raw material has a unique spatial structure (with a large aspect ratio and specific surface area) and excellent properties (high strength, high refractoriness, etc.). Polycarboxylic acid is used as a cross-linking agent to enhance the bonding force between inorganic halloysite and organic cellulose. The sol-gel method and CO 2Supercritical drying technology is used to prepare modified halloysite / cellulose composite aerogel with certain mechanical strength and excellent flame retardant properties, and its compressive strength reaches up to 3.6MPa. After the fire test, the compressive strength is 2.3MPa. In the aerogel of the present invention, cellulose is entangled and cross-linked with modified halloysite as the skeleton, which improves the mechanical properties of the material. At the same time, the addition of halloysite enriches the mesoporous structure in the cellulose aerogel, so that a large amount of non-circulating air inside hinders the mutual flow and transfer of heat. After the fire test, cellulose forms a thick carbon layer on the surface of the halloysite skeleton, which reduces the entry of oxygen and plays a good flame retardant effect.
[0052] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a reinforced flame-retardant cellulose aerogel material, characterized in that: The following steps are involved: S1, preparing a polycarboxylic acid solution with polycarboxylic acid, a catalyst and water as raw materials, placing halloysite in the polycarboxylic acid solution and stirring, and then calcining and post-treating to obtain polycarboxylic acid-modified halloysite; S2, adding polycarboxylic acid modified halloysite to the cellulose solution to obtain a mixed solution, subjecting the mixed solution to an aging replacement treatment to obtain a wet gel; and drying the wet gel to obtain a reinforced flame-retardant cellulose aerogel material.
2. The method for preparing the reinforced flame-retardant cellulose aerogel material according to claim 1, characterized in that: In step S1, the concentration of the polycarboxylic acid in the polycarboxylic acid solution is 1.0 mol / L to 1.1 mol / L, the mass concentration of the catalyst is 4 to 7%; and the mass ratio of halloysite to the polycarboxylic acid solution is 1:(18 to 22).
3. The method for preparing the reinforced flame-retardant cellulose aerogel material according to claim 1, characterized in that: In step S1, the polycarboxylic acid includes glutaric acid or adipic acid; and the catalyst includes sodium hypophosphite.
4. The method for preparing the reinforced flame-retardant cellulose aerogel material according to claim 1, characterized in that: In step S1, the halloysite is placed in a polycarboxylic acid solution, stirred for 1 to 2 hours, dried, and then calcined at 150 to 180° C. for 5 to 10 minutes.
5. The method for preparing the reinforced flame-retardant cellulose aerogel material according to claim 1, characterized in that: In step S1, the post-treatment includes washing and drying; the drying temperature is 80-100°C.
6. The method for preparing the reinforced flame-retardant cellulose aerogel material according to claim 1, characterized in that: In step S2, the mass ratio of the polycarboxylic acid-modified halloysite to the cellulose in the cellulose solution is (5-20):
100.
7. The method for preparing the reinforced flame-retardant cellulose aerogel material according to claim 1, characterized in that: In step S2, the preparation step of the cellulose solution includes: precooling the alkaline urea aqueous solution to -8 to -16 ° C and storing it for 2 to 4 hours, then placing cellulose in the precooled alkaline urea aqueous solution, stirring at -2 to -6 ° C for 1 to 2 hours to obtain a dissolved cellulose solution; the mass ratio of the alkaline urea aqueous solution to the cellulose is 600: (18 to 24).
8. The method for preparing the reinforced flame-retardant cellulose aerogel material according to claim 7, characterized in that: The alkaline urea aqueous solution comprises NaOH / urea / water solution, and the mass ratio of NaOH, urea and water is (6-8): (10-14): (78-86); The cross-sectional size of the cellulose is 5 to 20 nm, the length is 10 to 1000 nm, and the aspect ratio is (1 to 100):
1.
9. The method for preparing the reinforced flame-retardant cellulose aerogel material according to claim 1, characterized in that: In step S2, the conditions for mixing the polycarboxylic acid-modified halloysite and the cellulose solution include: mixing for 30 to 60 minutes at an ultrasonic power of 50 to 300 W; The aging replacement treatment is to place the mixed solution in an alcohol solvent and age it at room temperature for 12 hours to 24 hours to form a wet gel; the alcohol solvent includes an ethanol solution or tert-butyl alcohol with a concentration of more than 95%; The drying method includes CO2 supercritical drying.
10. The reinforced flame-retardant cellulose aerogel material prepared by the preparation method according to any one of claims 1 to 9.